Analisis Konten Dakwah Salat Pada Reels Instagram @Adzzom Dalam Perspektif Hadis - Naj'ma; Nasrulloh (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
The development of social media, particularly Instagram Reels, has opened up new spaces for Islamic preaching in the digital era. Although research on digital da'wah has received considerable attention, studies specifically addressing the analysis of prayer-themed content on Instagram Reels and its alignment with hadith perspectives remain limited. This study aims to analyze the form and content of prayer da'wah on Instagram Reels @adzzom, examine the digital da'wah strategies employed to reach Generation Z audiences, and assess the relevance of the messages to authentic hadith concerning prayer. This study employed a qualitative approach using content analysis method with a purposive selection of five viral Reels from the @adzzom account as the primary data source. Secondary data were drawn from hadith collections (Sahih Al-Bukhari, Sahih Muslim, Sunan Al-Tirmidzi, Musnad Ahmad), da'wah and Islamic communication literature, and journals. Data were analyzed using Miles and Huberman's model of data reduction, data display, and conclusion drawing/verification. The findings indicate that @adzzom's content encompasses three main dimensions; ‘aqidah (prayer as obligation and Muslim identity), shari'ah (encouragement to pray on time), and akhlaq (motivating repentance and return to prayer) delivered through emotional narratives, storytelling techniques, relatable language for Gen Z, and optimized visual and audio elements. The conclusion affirms that @adzzom successfully translates hadith values into effective digital content language. The implications include theoretical contributions to the understanding of Living Hadith in digital contexts and practical recommendations for Islamic educational institutions and digital preachers in designing more effective digital da'wah strategies for Generation Z.